2022
DOI: 10.1111/trf.17225
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A virus (HAV) RNA detection in Polish blood donors and likely transmissions through blood components during the 2017–2019 epidemic

Abstract: Background In Poland, hepatitis A virus (HAV) RNA screening was performed in plasma for fractionation usually immediately before shipment. Objective Our goal was to study epidemiology, rate of transfusion transmitted HAV during epidemic (2017–2019), and viral characteristics of infected plasma donors. Study Design and Methods HAV RNA was tested in 1,866,590 donations from 1,210,423 donors using RT‐PCR in mini pools of 96 (MP96) or TMA in MP16. Virological characteristics included RNA level (RL), antibody testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Although no studies in South America have examined the risk of HAV transmission through blood products, transfusion transmitted HAV infection has been demonstrated during outbreak periods in Europe, highlighting a new associated risk. 24,25…”
Section: Epidemiology: Brief History Of the Circulation Pattern Chang...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although no studies in South America have examined the risk of HAV transmission through blood products, transfusion transmitted HAV infection has been demonstrated during outbreak periods in Europe, highlighting a new associated risk. 24,25…”
Section: Epidemiology: Brief History Of the Circulation Pattern Chang...mentioning
confidence: 99%
“…Additionally, the risk of HAV transmission through blood transfusion should be considered in our region during periods of increased incidence. Although no studies in South America have examined the risk of HAV transmission through blood products, transfusion transmitted HAV infection has been demonstrated during outbreak periods in Europe, highlighting a new associated risk 24,25 …”
Section: Epidemiology: Brief History Of the Circulation Pattern Chang...mentioning
confidence: 99%
“…Sulkowska et al demonstrated transfusion transmission of HAV for two recipients by two window-period donations with RLs of between 5.3 and 6.5 log 10 IU/mL, although it is unclear what the total RL transfused was and the serostatus of the recipients at the time of transfusion. With declining incidence of anti-HAV antibodies (both natural and vaccineinduced) in Europe and higher RLs in donors than previously reported, 1,5 in real terms-at the copy number level, there is still much to learn about transfusion transmission of HAV. This includes minimum RLs that can result in transmission and the effect of existing anti-HAV antibodies in recipients.…”
mentioning
confidence: 94%
“…We read with interest the report by Sulkowska et al, about the characterization of hepatitis A virus (HAV) RNA-positive blood donations during the 2017-2019 epidemic in Poland. 1 Two nucleic acid amplification technique (NAT)-based methods were used to screen the Polish donations for HAV RNA, that is, transcription mediated amplification (TMA) or real-time reverse transcription polymerase chain reaction (rRT-PCR) using systems provided by Gen-Probe Incorporated/Hologic Inc. or Roche Molecular Systems Inc., respectively. Dependent upon platform, the TMA assay had a sensitivity (95% limit of detection-LOD) of 0.87-1.06 International Units (IU)/mL and the PCR assay a sensitivity of 1.06-1.1 IU/mL.…”
mentioning
confidence: 99%
“…Bununla birlikte, gelişmiş ülkelerde bildirilen yeni birkaç salgında kontamine gıdaların rolü olduğu gösterilmiştir (3) . Viremik fazdaki enfekte hastalar, kan nakliyle hastalığı nadir de olsa bulaştırabilir (4) .…”
Section: Introductionunclassified